The influence of discipline and training strategies on employee productivity at PT. Aerofood Indonesia Surabaya unit - Yasinta Asni Hayati; Arif Hidayat (Jurnal Mantik, 2026)
Employee discipline and training strategies are very important components in human resource management, which aims to increase knowledge and productivity. This study aims to determine the effect of discipline and training strategies on employee productivity at PT. Aerofood Indonesia Unit Surabaya. Factors that influence employee productivity include work discipline and training strategies implemented by the company. This study uses a quantitative approach with an explanatory research type. The population in this study were all 334 employees of PT. Aerofood Indonesia Unit Surabaya, with a sample of 77 respondents obtained using the Simple Random Sampling technique through the Slovin formula. Data collection techniques were carried out through observation, questionnaires, and documentation. Data analysis was conducted through validity and reliability assessments, classical assumption testing, multiple linear regression analysis, hypothesis testing using t-tests and F-tests, and determination coefficient (R²) analysis with the assistance of SPSS version 21 software. The results of the study indicate that discipline has a positive and significant effect on employee productivity, training strategies have a positive and significant effect on employee productivity, and discipline and training strategies simultaneously have a positive and significant effect on employee productivity at PT. Aerofood Indonesia Unit Surabaya. The results of this study are expected to be a consideration for companies in increasing employee productivity through improving work discipline and implementing effective training strategies